Reading strategies that work teaching your students to become better readers - Robb, Laura (New York Scholastic Professional Books, 1996)
Teaching ideas to help students learn reading strategies which are intended to develop their skills in and enjoyment of reading.
Keywords: Reading comprehension -- Study and teaching (Elementary); Reading (Elementary)